Social actor representation of the missing Malaysia Airlines Flight MH370 in the Malaysian and foreign news reports: a critical discourse analysis - Alias, Arlini; Mohd Nasir, Nora (Australian International Academic Centre PTY.LTD., 2019)
The objective of this study is to examine the linguistic representation of social actors in the selected Malaysian and foreign news reports on the circulated event of the missing MAS flight MH370. Despite extensive studies of news discourse, less attention is paid on how news event are speculated and the extent the social actors are relegated. Hence, the study explores the role of newspaper editorials in promoting stereotypical depictions through the representation of self- and other- in their reporting of the MH370 tragedy. The study retrieved a total of fifty (50) news reports of the missing MAS flight MH370 incident from ten news press, twenty-five (25) published by five local (Malaysian) English newsagents: The Star, New Straits Times, Sun Daily, Malaysian Insider and Malaysiakini, and twenty-five (25) others from five foreign newsagents: Daily Mail (UK), The Guardian (UK), Washington Post, New York Times and USA Today. The corpora were collected from March 8, 2014, to November 5, 2014, and analysed using Van Dijk’s (1998) Ideological Square framework, as well as Reisigl and Wodak (2000) Discursive Strategies. The analysis of this study discovers evidence of the “intergroup bias” made by the selected news press in representing the MH370 social actors. The selected news press displays an overt preference for own group and obvious demotion of the other group. The study also reveals the occurrence of lexicalization of the ‘other’ in the foreign news reports indicating positive representation of their in-group and exhibiting apparent disapproval of the actions by the outgroup. On the other hand, the analysis also reveals an impartial representation of the MH370 social actor by the local news press both for in-group and out-group. Key words: Aviation Crisis, MH370, News Discourse, Social Actor Representation